Faculty Members’ Communication Needs with Regards to Technology - Afam Uzorka (Commonwealth of Learning, 2021)
Educators are interested in the impact of technology on education and are supported by regulatory bodies promoting technology standards, recruiters seeking teachers with technology skills, legislated technology in the curriculum, and a demand for a technology skilled workforce. In response to the interest in technology in education, and faculty members incorporating technology in their work, this study was launched to investigate the communication needs of faculty members. This qualitative study selected a convenience sample of 120 faculty and administrators. Using an interview guide, interviewers met with 100 participants. Data was transcribed and entered into a database for analysis. Findings reported were about technology in communication. Concluding statements report that participants use technology in their communication. Faculty members look to early enablers to share best technology practices.